Pictures from the sea : the role of marine imagery and artefacts in the Bronze Age Aegean - Saunders, Emma (Trinity College (Dublin, Ireland). Department of Classics, 2008)
The Minoan civilisation which flourished on Crete in the Bronze Age delighted in depicting sea creatures in art. The marine world featured in every artistic medium and had great longevity within the Minoan artistic repertoire. While specific genres of marine art such as the LM IB ceramic Marine Style have been studied in depth, there is no single work tracing the development of marine imagery across the artistic media or examining the social functions of marine imagery and artefacts. Furthermore, the reasons for the popularity of marine imagery in Minoan art have traditionally been explained in purely economic terms, as the ‘natural’ outcome of the practical importance of the sea to Minoan life. This does not explain why the Minoans developed this artistic genre while other island communities did not. It is my contention that the social role of the marine world, its cultural, religious and symbolic importance, was a key factor influencing its portrayal in art. This thesis explores this issue by examining the social, religious and funerary associations of marine imagery and artefacts in the Bronze Age Aegean. It will also examine the development of marine motifs and the marine biological basis to the depictions (in terms of physical form, behaviour and habitat).
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin